Optimization of the Natural Disaster Mitigation Website (Gancana) as a Medium for Disaster Mitigation Socialization to Improve Preparedness of the Aceh Community - Muhammad Kautsar; Farouq Ahmed Ashim (Yayasan Hisnul Muslim Lombok, 2024)
This study aims to evaluate the effectiveness of the